CANCER SCREENING IN BRAZIL: GUIDELINES, CHALLENGES, AND PERSPECTIVES WITHIN THE UNIFIED HEALTH SYSTEM (SUS) (Editora Impacto Científico, 2025)
This chapter analyzes screening programs for breast, cervical, and colorectal cancers offered by Brazil's Unified Health System (SUS). The objective is to present official guidelines, discuss implementation, and identify key challenges. The methodology consisted of an analytical review of official documents from the Ministry of Health and the National Cancer Institute (INCA), supplemented by scientific literature. The results indicate a recent and significant change in breast cancer screening policy, which expanded the age range for organized screening (50 to 74 years) and now guarantees access to screening for women aged 40 to 49 years on demand. For cervical cancer, the recent and transformative transition from Pap smears to HPV DNA testing as the primary screening method for women aged 25 to 64 stands out. In contrast, for colorectal cancer, the current strategy is early diagnosis, without an organized population screening program. The discussion highlights significant cross-cutting challenges, such as profound regional inequalities in access, low program coverage, and a persistent gap between policy formulation and healthcare practice. The new guideline for breast cancer, while expanding access, also exposes a notable technical divergence with INCA and poses new implementation challenges for the healthcare network. It can be concluded that, despite the progress made in terms of guidelines, the effectiveness and equity of programs depend critically on strengthening health system management, improving the quality of primary care, and overcoming structural barriers to ensure that the benefits of early detection reach the entire population.DOI: https://doi.org/10.56238/edimpacto2025.028-023